# Cálculo Diferencial

Regla general de derivación:

( ) ( )
x
x f x x f
dx
dy
x ∆
− ∆ +
=
→ ∆ 0
lim

FÓRMULAS FUNDAMENTALES PARA LA DERIVACIÓN
DE ALGUNAS FUNCIONES:
( )
0 =
dx
c d
( = c constante) ( )
dx
du
e e
dx
d
u u
=
( )
1 =
dx
x d
( )
dx
dv
u u
dx
du
vu u
dx
d
v v v
ln
1
+ =

( )
dx
dw
dx
dv
dx
du
w v u
dx
d
± ± ± = ± ± ± ... ...
dx
dv
dv
dy
dx
dy
⋅ = (Regla de la cadena)
( )
dx
du
c
dx
cu d
= ( )
dx
du
u u sen
dx
d
cos =
( )
dx
du
v
dx
dv
u
dx
uv d
+ = ( )
dx
du
u sen u
dx
d
− = cos
( )
1 −
=
n
n
nx
dx
x d

( )
dx
du
u u tg
dx
d
2
sec =
( )
dx
du
nu
dx
u d
n
n
1 −
=
( )
dx
du
u u ctg
dx
d
2
csc − =

− =
|
.
|

\
|
dx
dv
u
dx
du
v
v v
u
dx
d
2
1
( )
dx
du
u tg u u
dx
d
⋅ = sec sec
dx
du
c c
u
dx
d 1
=
|
.
|

\
|
( )
dx
du
u ctg u u
dx
d
⋅ − = csc csc
( )
dx
du
u
u
dx
d
2
1
=
( )
dx
du
u
u sen
dx
d
2
1
1
1

=

( )
dx
du
u m
u
dx
d
m m
m
1
1

= ( )
dx
du
u
u
dx
d
2
1
1
1
cos

− =

( )
dx
du
vz
dx
dv
uz
dx
dz
uv uvz
dx
d
+ + = ( )
dx
du
u
u tg
dx
d
2
1
1
1
+
=

( )
dx
du
u
u
dx
d 1
ln = ( )
dx
du
u
u ctg
dx
d
2
1
1
1
+
− =

( )
dx
du
u
e
u
dx
d log
log =
( )
dx
du
u u
u
dx
d
1
1
sec
2
1

=

( )
dx
du
a a a
dx
d
u u
ln =
( )
dx
du
u u
u
dx
d
1
1
csc
2
1

− =